Preliminary methodology and results for root biomass sampling on the Pawnee site - Bartos, Dale Lee, author; Hughes, Joseph, author; Natural Resource Ecology Laboratory, Colorado State University, publisher (Colorado State University. Libraries, 1969)
Biweekly sampling of root biomass, organic matter, and crown materials was conducted at the Pawnee Site during the summer of 1969. The biomass data collected are presented here with means and standard deviations. These data will be utilized to determine future methods of sampling.
Keywords: data sampling; Pawnee National Grasslands; root biomass; Central Plains Experimental Range; Biomass -- Colorado; Roots (Botany) -- Colorado